A thermodesorption study of the chemisorption of thiophene on sulfided cobalt-molybdenum and industrial aluminum-cobalt-molybdenum catalysts; Bulletin of the Academy of Sciences of the USSR, Division of chemical science; Vol. 30, iss. 3 - Erofeev V. I. Vladimir Ivanovich (Physical chemistry, 1981)
Title screen